Genetic testing and prevention of hereditary cancer at the MMCI--over 10 years of experience - Foretova, L; Petrakova, K; Palacova, M; Kalabova, R; Svoboda, M; Navratilova, M; Schneiderova, M; Bolcak, K; Krejci, E; Drazan, L; Mikova, M; Hazova, J; et al. (Klinicka onkologie, 2010)
Hereditary cancer syndromes are frequently seen in young cancer patients and patients with a positive family history. Genetic testing is important for the identification of high-risk individuals, and for the early introduction of specialized preventive care or prophylactic surgeries. High-risk tumour suppressor genes (BRCA1 and BRCA2) and DNA repair genes (MLH1, MSH2 and MSH6) are responsible for a substantial part of hereditary breast, ovarian and colorectal cancer. Other hereditary cancers are seen less frequently, but genetic testing has increased for many other site-specific cancers and complex syndromes. Genetic centres and molecular genetic laboratories are located mostly within university or regional hospitals. Some genetic centres are private. It is highly recommended (Czech Society for Medical Genetics) that all laboratories are accredited according to ISO 15,189 and that genetic testing of hereditary cancer syndromes is indicated by medical geneticists. The indication criteria and prevention strategies were published in Supplement 22 of Clinical Oncology 2009 (in Czech). Preventive care for high-risk individuals is organized by thirteen Oncology Centres, which provide most of the oncology care in the Czech Republic. Genetic testing and preventive care for high-risk individuals and mutation carriers is covered by health insurance. The molecular genetic laboratory at the MMCI provides molecular genetic testing of BRCA1, BRCA2, CHEK2 for hereditary breast/ovarian cancer, MLH1, MSH2, MSH6 for Lynch syndrome,TP53 for Li-Fraumeni syndrome, CDKN2A for familial malignant melanoma syndrome and CDH1 gene for hereditary diffuse gastric cancer. Other syndromes are tested in specialized laboratories elsewhere.The use of genetic testing is increasing because of more frequent referrals from oncologists and other specialists and the increasing variety of genes tested. However, in some patients the testing is not recommended and other family members are dying because of the late diagnosis of hereditary syndrome. Greater awareness of the importance of genetic testing in oncology is needed.
Keywords: mutace; genetické testování; rodokmen; Genetic Testing; Neoplastic Syndromes, Hereditary; lidé; Pedigree; dědičné nádorové syndromy; Mutation; genetická predispozice k nemoci; Genetic Predisposition to Disease; Humans